2012
DOI: 10.4049/jimmunol.1102029
|View full text |Cite
|
Sign up to set email alerts
|

The Calcineurin B Subunit (CnB) Is a New Ligand of Integrin αM That Mediates CnB-Induced Apo2L/TRAIL Expression in Macrophages

Abstract: We showed previously that the calcineurin B subunit (CnB) plays an important role in activation of peritoneal macrophage, but the underlying mechanism remained unknown. To examine whether there is a CnB receptor on peritoneal macrophages, we performed the radioligand binding assay of receptors. The receptor saturation binding curve demonstrated high-affinity and specific binding; the maximum binding was 1090 fmol/105 cells, and the Kd was 70.59 pM. Then, we used a CnB affinity resin to trap potential receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 59 publications
1
9
0
1
Order By: Relevance
“…Calcineurin is one of the most important proteins in the immune system. The calcineurin B subunit has been shown to activate macrophages and stimulate cytokine production by itself, regardless of the calcineurin A subunit [17,18,19,20]. This protein is thus a possible candidate for stimulation of extra-renal 1α-hydroxylation.…”
Section: Discussionmentioning
confidence: 99%
“…Calcineurin is one of the most important proteins in the immune system. The calcineurin B subunit has been shown to activate macrophages and stimulate cytokine production by itself, regardless of the calcineurin A subunit [17,18,19,20]. This protein is thus a possible candidate for stimulation of extra-renal 1α-hydroxylation.…”
Section: Discussionmentioning
confidence: 99%
“…CD11b is found primarily on innate immune cells of myeloid lineage, and plays important roles in cell adhesion, migration, chemotaxis, and phagocytosis [41]. Melanoma cell extravasation was decreased following a reduction in integrin α M β 2 levels on polymorphonuclear neutrophils by functional blocking of IL-8 binding [42], implicating CD11b in melanoma metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The antitumor effect of CnB is closely related to its function in immune regulation because we also found that CnB can mature and activate dendritic cells and enhance antigen presentation and thus function as a novel adjuvant of cancer vaccines (22) and the Engerix-B ® HBV vaccine (23). Additionally, CnB can activate macrophages by binding to integrinαM, and then promotes the expression and secretion of TNF-related apoptosis-inducing ligand (TRAIL), a specific pro-apoptotic cytokine (24,25). Further, synergistic interaction between CnB and IFN-γ enhances macrophage antitumor activity by polarize tumor associated macrophages to M1-phenotype (26).…”
Section: Introductionmentioning
confidence: 97%